2020
DOI: 10.48550/arxiv.2005.08508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Chaos in Topologically Massive Gravity

Yan Liu,
Avinash Raju

Abstract: We study quantum chaos of rotating BTZ black holes in Topologically Massive gravity (TMG). We discuss the relationship between chaos parameters including Lyapunov exponents and butterfly velocities from shock wave calculations of outof-time-order correlators (OTOC) and from pole-skipping analysis. We find a match between pole-skipping and the OTOC results, in the high temperature and µ ≥ 1 regime of the gravitational Chern-Simons coupling. Coincidentally, this is also the regime where the chaos parameters sati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…where λ L = 2πT is the Lyapunov exponent for holographic theories and v B is the butterfly velocity. Thus this location seems to be connected to the chaotic properties of holographic systems [12-14] 1 , which is the case even in the presence of stringy corrections [17] (see [18][19][20][21][22] for further examples).…”
Section: Introductionmentioning
confidence: 99%
“…where λ L = 2πT is the Lyapunov exponent for holographic theories and v B is the butterfly velocity. Thus this location seems to be connected to the chaotic properties of holographic systems [12-14] 1 , which is the case even in the presence of stringy corrections [17] (see [18][19][20][21][22] for further examples).…”
Section: Introductionmentioning
confidence: 99%
“…One important exception is provided by the study of rotating BTZ black holes, which are dual to a 1+1 dimensional CFT on a circle with a chemical potential for rotation. 2 In such a setting, the form of the OTOC was studied in [53,54] (see also [55][56][57][58][59][60]), and in [61] it has been shown that a natural generalisation of pole-skipping applies for arbitrary values of rotation. Whilst the fact that pole-skipping continues to hold in this case is reassuring, and provides evidence that a hydrodynamic effective theory of chaos continues to apply, both the effects of rotation and the dual gravity description are particularly simple for 1+1 dimensional CFTs.…”
Section: Introductionmentioning
confidence: 99%
“…So the connection can be realized from the AdS/CFT correspondence. A list of several other works recently done on pole skipping phenomenon can be found in [31][32][33][34][35][36][37][38]. 2 In this paper we have considered a gravitational background with a spatial anisotropy as obtained in [40,41].…”
Section: Introductionmentioning
confidence: 99%